A staged purification process to remove heavy metal ions from wastewater using Rhizopus arrhizus - Ozer, A; Ekiz, HI; Ozer, D; Kutsal, T; Caglar, A (Elsevier Sci Ltd, 1997)
The adsorption of iron(III), lead(II) and cadmium(II) ions onto dry cells of Rhizopus arrhizus was investigated in a four-stage batch reactor. The adsorption in multi-stage reactors can be considered as a multi-stage equilibrium depending on the adsorption equilibrium and mass balance. The Freundlich and Langmuir adsorption isotherms were developed to evaluate the biosorptive uptake capacity of the biomass. The Freundlich and Langmuir constants at optimum adsorption conditions were used to calculate the residual or adsorbed metal ion concentrations at equilibrium at each stage for a given volume of solution containing heavy metal ion/quantity of dried biomass (V-0/X) ratio. The experimental equilibrium values were compared with the values obtained from Freundlich and Langmuir isotherm equations. These results showed that the increase in biomass quantity or the decrease of V-0/X ratios affected the quantities of iron, lead and cadmium removed from aqueous solution. (C) 1997 Elsevier Science Ltd.
Keywords: adsorption; heavy metal ions; wastewater; biomass